Characteristics of Thermal Front in the Tropical Waters of Eastern Indian Ocean - Soni Rohima Daulay; Tengku Ersti Yulika Sari; Usman Usman; Romie Jhonnerie (Jurnal Perikanan Universitas Gadjah Mada, 2019)
This study aims to elucidate spatio-temporal variability of the thermal front in the eastern tropical Indian Ocean of the western Sumatera. The research was conducted during November 2017- February 2018. The Single Image Edge Detection (SIED) was applied to daily sea surface temperature (SST) data of 2016 of the level-3 Aqua Moderate Resolution Imaging Spectroradiometer (MODIS) for the detection of thermal front. The number of the thermal front events during 2016 were 167 days. The distribution and frequency of thermal front mostly found in January, i.e. 23 days with SST mean of 30.3ºC. Whereas the lowest distribution appeared in November and the lowest frequency observed in September, i.e. 6 days with the SST mean of 29.1ºC. The highest temperature range of thermal front is between 31.4-32.0ºC and the lowest ranged between 26.4-29.3ºC. The occurrences of thermal front were commonly found in the open ocean. The highest frequency occurred in January and the lowest took place in September with the longest duration of 3 days.